Clinical manifestations of nasoethmoid-central midface and lateral mid midface trauma: an analytical study - Munjal, Manish; Kanotra, Sonika; Munjal, Shubham; Chopra, Parth; Saggar, Vanshika; Kaur, Hardeep; Sandhu, Lovleen; Binepal, Tejbir Singh; Pillai, Anjana; Chopra, Hemant; Uppal, Sanjeev (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Patients with facial trauma were analyzed to determine the clinical presentation of fractures of the naso-ethmoid, mid and lateral face. Methods: 61 patients in the trauma unit of Dayanand Medical College were prospectively analyzed during a period of two years (August 2013 to August 2015). Results: Road traffic accidents were the major cause of fractures (72.13%) followed by assaults (14.75%) and falls (8.19%). The age group commonly affected was 21-30 years (54.09%) followed by 31-40 years (13.11%). Facial fractures were more in males, the females being 5 times less at risk. Epistaxis, swelling, tenderness, nasal obstruction, external nasal deformity and crepitus were noted in almost all patients. Ecchymosis, telecanthus and CSF rhinorrhea were noted in 90.9%, 72.7%, and 18.18% respectively. 90% presented with circumorbital ecchymosis, facial edema and anterior open bite. Other symptoms were epistaxis (81%), infraorbital nerve anesthesia and surgical emphysema (47.6%) and lengthening of face (42.8%). The commonest presentation was circumorbital ecchymosis (95.5%), subconjuctival hemorrhage (85.7%), flattening of cheek and step deformity at the infraorbital margin (81%). Facial edema was seen in 76% and trismus in 42.9%. Conclusions: Common symptoms and signs of nasoethmoid fractures included epistaxis, swelling and tenderness, nasal obstruction, external nasal deformity and crepitus in all patients, circumorbital ecchymosis in 90% and telecanthus in 73%.